Cultural landscapes: the Llollelhue hydroelectric power station called La Turbina [The Turbine] in the city of La Unión - Vásquez, Virginia; Valdebenito, Galo; Ogalde, Manola (Revista de Urbanismo, 2018)
As an element of memory and social capital construction, Infrastructure projects constitutes an exquisite model of sovereignty and integral control of the territory that gets materialised in a social memory, through a cultural landscape. This paper is set to explore, in a qualitative dimension, the development of a local and cultural landscape; the changes that has been produced in the territory as the physical matrix, as well as the memory of the community from the city of La Unión (Chile), after the installation of the Llollelhue hydroelectric plant, also known as La Turbina [the turbine]. The architecture, the building that control the water supply, still remain as an important part of the city landscape, with heritage attributes and current profitable vocation.The methodology uses a multiple-scales approach of landscape and social memory, linked as an element of the sociocultural dimension. The preliminary results point to characterize a matrix of the collaborative dynamics, between landscape and society. Thus, this cultural landscape developed by La Turbina, is defined as a heritage system that conjugates features that go far beyond the limits of a building and they refer an epistemology of territory.